Hard and soft tissue manipulation to optimize the peri-implant aesthetics – case report - Leandro de Carvalho Cardoso; Danielly Vieira Martins; Ricardo Alexandre Zavanelli; Renata Schreibe; Tiago Oliveira Tavares; João Batista de Souza (Revista Sul-Brasileira de Odontologia, 2014)
The demand for aesthetic results in oral rehabilitation by dental implants in the anterior area constitutes a major challenge for dentists. Objective: The purpose of this paper was to report the management of hard and soft tissues to optimize the aesthetics of a single implant at anterior area. Case report: The patient underwent autogenous block bone graft surgery, Morse taper implant installation, peri-implant soft tissue manipulation through the “roll on” technique, provisional tooth and prosthetic finishing with metal free implantsupported crown. Conclusion: After three years of follow-up, this paper strongly suggests that the combination of bone with gingival techniques proved to be essential for obtaining predictability and adequate esthetic results.